Investigação de Zika vírus em gestantes exantemáticas: identificação de positividade viral prolongada - Oliveira, Thais Santana de (2018)
Zika virus (ZIKV) has recently emerged causing epidemics that impacted in the Americas, Africa and Asia and, despite transmission by arthropod vectors, sexual and maternal-child transmission have already been reported. Infection during pregnancy has been associated with congenital malformations, including microcephaly. Although we have advanced in ZIKV study, there are still gaps regarding the pathogenesis of this infection. The present study objected to investigate the occurrence of ZIKV in cases of exanthematic pregnant women evaluating prolonged viral detection in urine and blood samples. The population consisted of 68 pregnant women, of whom 57 were followed up through periodic consultations, and blood and/or urine samples were collected at each visit. Samples were subjected to detection of viral RNA by real-time RT-PCR using the commercial kit, primers and probe specific for the target region to structural protein E. Positivity rate of 51.5% for ZIKV was observed (35/68). The samples colected of follow up patients, different patterns of prolonged viral detection in the blood and/or urine were identified in 19.3% of pregnant women. In urine samples, viral RNA was detected up to 147 days after onset of symptoms and in the blood up to 187 days after the onset of rash. Among the pregnant women with prolonged detection profile, the majority presented the exanthematic episode at the first and second gestational trimester. Prolonged detection for ZIKV has been reported in other clinical specimens although many questions remain. In this scenario, the information obtained in the present study contributes to the knowledge about the process of the pathogenesis of Zika virus infection in infected pregnant women.